Re‐osseointegration following reconstructive surgical therapy of experimental peri‐implantitis. A pre‐clinical in vivo study. Issue 5 (3rd May 2019) - Almohandes, Ahmed; Carcuac, Olivier; Abrahamsson, Ingemar; Lund, Henrik; Berglundh, Tord
Abstract: Objective: To evaluate the effect of bone substitute materials on hard and soft tissue healing in reconstructive surgical therapy of experimental peri‐implantitis at implants with different surface characteristics. Material and methods: Six female, Labrador dogs were used. 3 months after tooth extraction, four implants with two different surface characteristics (A and B) were installed on each side of the mandible. Experimental peri‐implantitis was induced 3 months later. During surgical treatment of peri‐implantitis, the implants were cleaned with curettes and cotton pellets soaked in saline. The implant sites were allocated to one of four treatment categories; (a) Group C; no augmentation, (b) Group T1; bone defect filled with deproteinized bovine bone mineral (c) Group T2; bone defect filled with a biphasic bone graft material, (d) Group T3; bone defect filled as T1 and covered with a collagen membrane. Clinical and radiological examinations were performed, and biopsies were obtained and prepared for histological analysis 6 months after peri‐implantitis surgery. Results: Implant B (smooth surface) sites showed significantly (a) larger radiographic bone level gain, (b) enhanced resolution of peri‐implantitis lesions, and (c) larger frequency of re‐osseointegration than implant A (moderately rough surface) sites. Implant B sites also showed superior preservation of the mucosal margin. Differences between bone substitute materials and control procedures were overall small with limited advantages for T1 and T2 sites. Conclusion: Healing following reconstructive surgical treatment of experimental peri‐implantitis was superior around implants with a smooth surface than implants with a moderately rough surface. Benefits of using bone substitute materials during surgical therapy were overall small.